Aqueous Polymerization of Vinyl Monomers Initiated by Mn(III)-Amino Acid Chelating Agents - Siva Kumar, G.; Krishnaveni, N.; Umayavalli, M.; Manickam, S.P.; Ratnasabapathy, S. (Asian Journal of Chemistry, 2012)
The polymerization kinetics of acrylamide initiated by the redox pairs i.e., tris-acetatomanganese(III)dihydrate-ethylenediaminetetraacetic acid and in dilute sulphuric acid medium was investigated. The rate of polymerization (Rp) was proportional to [AM]1.3, [EDTA]0.6 and inverse dependence to [Mn(III)] for acrylamide-Mn(III)-EDTA system and [AM]1.2, [EDTA]0.3 and inverse dependence to [Mn(III)] for acrylamide-Mn(III)-nitriloacetic acid system. The rate of manganic ion disappearance Rm, was directly proportional to [Mn(III)] and [NTA] but independent of monomer for both the systems. Both Rp and Rm were not affected by the changes in [H+], ionic strength, added Mn(II) and Rp decreased with the addition of sodium nitrate. The activation energy was evaluated by using Arrhenius plot. Suitable mechanism has been proposed to explain the observed kinetic data.